The Effect of Financial Performance on Sharia Stock Prices with Sharia Market Sentiment as a Moderating Variable: A Study of Manufacturing Companies in ISSI 2019–2024 - Umiafifah Syafiq Dwi Cahyaningrum; Mohammad Edman Syarief; Ira Novianty (Journal of Economics and Business UBS, 2026)
This study aims to analyze the effect of financial performance on Sharia-compliant stock prices, with Sharia market sentiment as a moderating variable, in manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) for the period 2019–2024. Financial performance is represented by Return on Assets (ROA), Net Profit Margin (NPM), Earnings per Share (EPS), and Debt to Equity Ratio (DER), while Sharia-compliant stock prices are used as an indicator of market response to company performance. Sharia market sentiment is measured using Google Trends data, which reflects the level of investor attention and interest in Sharia stocks. This study employs a quantitative approach and panel data regression method, with secondary data obtained from company financial reports and official capital market publications. The panel regression model was selected using the Chow Test, Hausman Test, and Lagrange Multiplier Test to obtain the most appropriate estimation model. This study is complemented by classical assumption tests and hypothesis testing to ensure the reliability of the research results. This study is expected to provide empirical evidence regarding the role of financial performance in determining Sharia stock prices and how Sharia market sentiment can strengthen or weaken this relationship. The results of this study are expected to contribute to the development of empirical literature in Islamic finance, particularly regarding the integration of fundamental factors and investor behavior. This research also provides practical implications for company management in improving financial performance.